2021
DOI: 10.3389/fmars.2021.663304
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Prevailing Hydrodynamics Around a Cold-Water Coral Colony Using a Physical and a Numerical Approach

Abstract: Framework-forming cold-water corals provide a refuge for numerous organisms and, consequently, the ecosystems formed by these corals can be considered as impressive deep-sea biodiversity hotspots. If suitable environmental conditions for coral growth persist over sufficiently long periods of time in equilibrium with continuous sediment input, substantial accumulations of coral mound deposits consisting of coral fragments and baffled sediments can form. Although this conceptual approach is widely accepted, litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…However, flume tank experiments and modeling studies highlighted the remarkable surface roughness of branching corals with large bottom drag coefficients (Monismith, 2007), which significantly slow down bypassing currents, both on colony-and reef-scale (e.g., Chang et al, 2009;Guihen et al, 2013;Johansen, 2014;Lowe and Falter, 2015;Mienis et al, 2019;Bartzke et al, 2021;Hennige et al, 2021). Hence, the baffling capacity of densely distributed coral frameworks on the mound's surface results in a low energy environment allowing fine suspended sediments to settle even under generally turbulent background conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, flume tank experiments and modeling studies highlighted the remarkable surface roughness of branching corals with large bottom drag coefficients (Monismith, 2007), which significantly slow down bypassing currents, both on colony-and reef-scale (e.g., Chang et al, 2009;Guihen et al, 2013;Johansen, 2014;Lowe and Falter, 2015;Mienis et al, 2019;Bartzke et al, 2021;Hennige et al, 2021). Hence, the baffling capacity of densely distributed coral frameworks on the mound's surface results in a low energy environment allowing fine suspended sediments to settle even under generally turbulent background conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, comparing surface sediments from coral mounds and near-by seafloor settings already revealed a relative enrichment of fine material on the mounds that was assumed to reflect (a) the winnowing of fine sediments from the seafloor next to the mounds and (b) their subsequent deposition on the mounds forced by coral baffling (Mullins et al, 1981;Paull et al, 2000;Wheeler et al, 2011). In addition, experimental and modeling studies have impressively shown how current velocities are reduced within CWC frameworks favoring the settlement of suspended sediments (e.g., Chang et al, 2009;Mienis et al, 2019;Bartzke et al, 2021;Hennige et al, 2021). However, detailed studies on the processes controlling sediment delivery and deposition on coral mounds and their impact on coral mound formation, notably over longer timescales, are still largely lacking.…”
Section: Introductionmentioning
confidence: 99%
“…We applied a simplified 2D transport-reaction model in order to investigate the effect of the ciliary flow on the O 2 concentration inside the tissue and within the coral boundary layer. The model approach does not consider 3D effects or changes in the topography of the coral, which might become substantial when investigating the turbulent flow field along an entire coral colony see for example Bartzke et al 80 However, on the scales of the investigated coral fragments, the topographical features where an order of magnitude smaller (21 -123 mm) than the observed vortices (typically around 1 mm) and were not a substantial factor within the experiments. It remains a task for future studies to investigate how O 2 is re-distributed along an entire coral colony and how topography and ciliary flow act in tandem for coral ventilation.…”
Section: Limitations Of the Model And Topography Effectsmentioning
confidence: 99%
“…In fact, many aquaria experimental studies have determined the presence of differential CWC growth rates under contrasting treatments of several environmental variables (e.g., temperature, pH and food supply) in relatively short periods of time 43 46 . According to experimental and numerical simulation studies, coral patches/reefs promote an alteration of the water flow and sediment transport in their vicinity 47 , enhancing particulate matter residence time and deposition, and ultimately affecting its availability within the reef itself 33 , 48 . Indeed, Mienis et al 33 demonstrated that, under realistic current speeds, reef patches promote higher flow velocities over the patch, whereas its wake is characterised by near-stagnant flows with reduced turbulence and vertical mixing.…”
Section: Introductionmentioning
confidence: 99%